Cover Feature: Lignin‐First Monomers to Catechol: Rational Cleavage of C−O and C−C Bonds over Zeolites (ChemSusChem 7/2022). Issue 7 (19th March 2022) - Wu, Xian; Liao, Yuhe; Bomon, Jeroen; Tian, Guilong; Bai, Shao‐Tao; Van Aelst, Korneel; Zhang, Qiang; Vermandel, Walter; Wambacq, Ben; Maes, Bert U. W.; Yu, Jihong; Sels, Bert F.
Abstract : The Cover Feature shows that two types of zeolites (BEA* and MFI) were used as catalysts (saws) to respectively break the C−O and C−C bonds of lignin‐first monomers obtained from soft wood. The developed catalytic strategy provides a new approach to produce catechol from renewable feedstocks. More information can be found in the Research Article by X. Wu et al .